Uniqueness of the concept of witness in Lukan writings within the biblical canon - Budiselić, Ervin (Langham Academic, 2024)
"In an age of relativism, tolerance and political correctness, the church is called to walk in the footsteps of Christ. As his witnesses, we must reject all forms of coercion and violence while simultaneously refusing to shy away from the authority and conviction that come from carrying his revelation. Dr. Ervin Budiselic examines the concept of "witnessing" in the writings of Luke, contextualizing it within the larger framework of Scripture's emphasis on revelation and testimony. Like Judaism, Christianity is a religion of revelation, where specific content must be preserved, passed on and proclaimed to others. Dr. Budiselic explores the communal nature of this calling, as well as its pneumatological implications within Luke's writings. Acknowledging the tendency within the Western church to emphasize moral transformation over physical, he reminds readers that Jesus's kingdom ministry was accompanied by deeds as well as words. He specifically engages the dangers of normalizing a gospel disconnected from the supernatural or the miraculous, as partnership with the Holy Spirit was central to the calling given to the early church. This book offers a prophetic message for the church today as it seeks to fulfill its calling to faithfully witness to the revelation of Christ." --